Anti-inflammatory effects of Hwang-Heuk-San, a traditional Korean herbal formulation, on lipopolysaccharide-stimulated murine macrophages. Issue 1 (December 2015) - Kang, Hye; Hong, Su; Kang, Kyung-Hwa; Park, Cheol; Choi, Yung
Abstract Background Hwang-Heuk-San (HHS), a Korean traditional herbal formula comprising four medicinal herbs, has been used to treat patients with inflammation syndromes and digestive tract cancer for hundreds of years; however, its anti-inflammatory potential is poorly understood. The aim of the present study was to investigate the anti-inflammatory effects of HHS using a lipopolysaccharide (LPS)-activated RAW 264.7 macrophage model. Methods The inhibitory effects of HHS on LPS-induced nitric oxide (NO), interleukin-1β (IL-1β) and tumor necrosis factor-α (TNF-α) production were examined using Griess reagent and enzyme-linked immunosorbent assay (ELISA) detection kits. The effects of HHS on the expression of inducible NO synthase (iNOS), IL-1β and TNF-α, their upstream signal proteins, including nuclear factor κB (NF-κB), mitogen-activated protein kinases (MAPKs), and activator protein (AP-1), were also investigated. Results A noncytotoxic concentration of HHS significantly reduced the production of NO, IL-1β and TNF-α in LPS-stimulated RAW 264.7 cells, which was correlated with reduced expression of iNOS, IL-1β and TNF-α at the mRNA and protein levels. HHS efficiently blocked the phosphorylation of MAPKs, especially that of extracellular signal-regulated kinase (ERK) and c-Jun NH2-terminal kinase (JNK) but not that of the p38 MAPK. The reduced production of inflammatory molecules by HHS was followed by decreased activity of NF-κB and AP-1. Conclusions These results suggest that HHS may offer therapeutic potential for treating inflammatory diseases accompanied by macrophage activation.